(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The scale insect fauna of Yemen is practically unknown to coccidologists. Systematic and faunistic research is being carried out to fill this gap. This paper reports on mealybug species collected on agricultural crops, namely grapevine, mango, guava, citrus, coffee and sorghum.